If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7d + -1d + -6d + 7 = 4d Reorder the terms: 7 + 7d + -1d + -6d = 4d Combine like terms: 7d + -1d = 6d 7 + 6d + -6d = 4d Combine like terms: 6d + -6d = 0 7 + 0 = 4d 7 = 4d Solving 7 = 4d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-4d' to each side of the equation. 7 + -4d = 4d + -4d Combine like terms: 4d + -4d = 0 7 + -4d = 0 Add '-7' to each side of the equation. 7 + -7 + -4d = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -4d = 0 + -7 -4d = 0 + -7 Combine like terms: 0 + -7 = -7 -4d = -7 Divide each side by '-4'. d = 1.75 Simplifying d = 1.75
| (4x+3)+(4x+3)+(7x)=16x-1 | | G-2/5= | | p^2-72=-14p | | x/-3=-10 | | 5-4(m+2)=-5m | | 18=19+x | | 5x-12-8x/2=4 | | 0.5x+0.6y=5.7 | | 0.5n-1.2n+0.2n=45.8-3.3 | | -2x-2-5x=10 | | 5n-37=3n-5 | | 27=3(5-x) | | 2(x+3)=5(x-7) | | 8x+10=y | | -(6-y)=25 | | (2x-3)/9 | | -36=x-124 | | -4(8x-3)-5x=-5 | | -36=x+124 | | -8(1-7v)=-456 | | 5a-2+6a= | | 6x-1/2=36 | | (4x+3)+(4x+3)+(3x-2)=6x | | 800=60x+2x^2 | | 7-5x=5x-6x+7 | | 8x+2(-4-5x)=-12 | | -3x=-2/3x-5/9 | | 5r-25=-5(5-6r) | | 1/2x=16=36 | | 8/5=32-× | | .2(4z+6)=36 | | 3b+7-2-5b= |